Penggunaan Model Team Assisted Individualization untuk Meningkatkan Hasil Belajar Peserta Didik - Haryati, Aat; Kamal, Mustopa (Jurnal Penelitian Pendidikan Islam, 2016)
This research is motivated by the low learning outcomes of students in social studies. This is because most of the daily test scores of students have not reached the minimum standard. Therefore, it is necessary to use models of Team Assisted Individualization in the social studies learning. The purpose of this study are: to improve the ability of teachers in preparing a lesson plan, to improve the ability of teachers to implement the learning process, and to improve the learning outcomes of students in social studies subject. Data collected using observational techniques, test, and descriptive analysis. The result showed that the using of Team Assisted Individualization learning model can improve learning outcomes of students in social studies.